2018
DOI: 10.1186/s13104-018-3874-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices and associated factors among diabetes patients attending the outpatient department in Bahir Dar, Northwest Ethiopia

Abstract: ObjectiveThe aim of this study was to assess diabetes self-care practice and associated factors among diabetes patients attending Felege-Hiwot Referral Hospital, Bahir Dar, Northwest Ethiopia.ResultPrevalence of desirable self-care behaviors toward Diabetes Mellitus was 28.4% (95% CI 24.0–32.7%). There were significant association between the combined treatment modality of tablet with insulin (AOR: 2.72; 95% CI 1.01, 7.40), primary and secondary education level (AOR: 4.82; 95% CI 1.88, 12.35 and AOR: 3.08; 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 12 publications
7
54
8
Order By: Relevance
“…A higher proportion of patients who were on oral hypoglycemic agents had inadequate diabetes-related self-care activities. The result is similar to the study conducted in Ethiopia that also found treatment modality as a significant predictor of self-care [30]. Also, our study revealed delayed wound healing in patients with inadequate diabetes-related self-care activities in comparison to the other group.…”
Section: Discussionsupporting
confidence: 90%
“…A higher proportion of patients who were on oral hypoglycemic agents had inadequate diabetes-related self-care activities. The result is similar to the study conducted in Ethiopia that also found treatment modality as a significant predictor of self-care [30]. Also, our study revealed delayed wound healing in patients with inadequate diabetes-related self-care activities in comparison to the other group.…”
Section: Discussionsupporting
confidence: 90%
“…This was consistent with studies conducted in the Oromia region, Adama (49.1%) (18), and southwest of Ethiopia (49.2%) (13). However, it was higher compared to other studies conducted in Bahir Dar, northwest of Ethiopia, which was only 28.4% (9) and Harar 39% (19). But, the nding of this study was lower than a study from in Nekemte, western Ethiopia 60.7% (8), This difference could be due to variation in cultural, and socio-economic aspects of the society as Ethiopia is a diverse country (20).…”
Section: Discussioncontrasting
confidence: 79%
“…This study found that those with no formal education were more likely to adhere to diabetes self-care practice. On the contrary, other studies found that the higher the educational status it is likely to have good self-care practice (9,13,19). This might be justi ed regardless of their educational status patient might adhere to self-care practices based on the information they receive from health care providers or the media.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Referring to the response rate, the lowest and the highest response rates were 95% and 100% consecutively. Furthermore, the prevalence of diabetics self-care practice falls between 28.4% and 76.8% from a study conducted in Amhara (27) and SNNPs(10) regions, respectively. All the studies incorporated were simple and analytical cross-section by design (Table 1).…”
Section: Characteristics Of Included Primary Studiesmentioning
confidence: 99%